(untitled) (Agroindustrial Science, 2023)
The objective of this study was to evaluate the incidence of roasting temperature (120, 130 and 140 °C) on the physical-chemical characteristics and husk alkaloids of three cocoa varieties (Forastero, Trinitario and CCN51) and their effect on the organoleptic properties of an infusion. The evaluation of the physical-chemical characteristics (humidity, pH and titratable acidity) was carried out according to INEN standards: 1676:2013; 1842:2013 and 381 respectively and alkaloid analysis (theobromine and caffeine) according to the reference method AOAC 980.14-1998, regarding the organoleptic analysis a 9-point hedonic test was used. This allowed determining that the roasting temperature significantly influences the physical-chemical characteristics and emphasizes that the values of the evaluated parameters decrease as the temperature rises. For alkaloids, it was shown that the type of cocoa husk had an impact on the content. In addition, high roasting temperature reduces theobromine and considerably increases caffeine. For the organoleptic analysis, it was determined that T1 (Forastero + 120 °C) obtained the highest scores in aroma, flavor and acceptability; in relation to color, T4 (Trinitario + 120 °C) stood out with the highest score. Thus, it is attributed that the presence of bitter, acid and astringent flavors in the husk is due to temperatures greater than or equal to 140 °C.